Ask Question
30 August, 06:34

X - 3y+z = 6

2x - бу - 2 = - 2

-x+y + 2 = 7

0
Answers (2)
  1. 30 August, 06:49
    0
    x = - 7 1/2

    y = - 5/2

    z = 11
  2. 30 August, 07:38
    0
    x = - 7 1/2

    y = - 5/2

    z = 11

    Step-by-step explanation:

    x - 3y+z = 6 (1)

    2x - бу - 2 = - 2 (2) 2x - 6y = - 2 + 2 = 0 (2x - 6y) / 2 = 0 x - 3y = 0 (4)

    -x+y + 2 = 7 (3) - x + y = 7 - 2 x - y = - 5 (5)

    Subtract (5) from (4), we have:

    (x - 3y) - (x - y) = 0 - (-5)

    x - 3y - x + y = 5

    -2y = 5

    y = - 5/2

    Replace y with (4), we have x = 3 * (-5/2) = - 15/2 (or - 7 1/2)

    Replace x with - 15/2 and y with - 5/2 in (1), we have z = 6 - (-15/2 - (-5/2)) = 6 + (15/2 - 5/2) = 6 + 5 = 11
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “X - 3y+z = 6 2x - бу - 2 = - 2 -x+y + 2 = 7 ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers